Market hurdles and cooperative pathways: Transforming smallholder dairy cattle farming in Tanga region, Tanzania - Fred Alfred Rwechungura; Felister Yakobo Tibamanya; Victoria Mugula (International Journal of Agricultural Research, Innovation and Technology, 2026)
This study investigates the determinants of cooperative participation among small-scale dairy farmers in Tanga Region, Tanzania, where cooperative involvement remains low despite its potential to enhance productivity and resilience. Grounded in Collective Action Theory (CAT), Social Capital Theory (SCT), and Diffusion of Innovations Theory (DOI), the study surveyed 302 dairy farmers using multistage sampling. Data were collected through structured questionnaires and analyzed using descriptive statistics and a Probit regression model. The results indicate that several factors significantly influence cooperative membership. Being male increases the likelihood of participation by 13 percentage points (p < 0.05), suggesting persistent gender disparities. Herd size and milk production both positively affect participation-each additional cow increases participation by 2 percentage points (p < 0.1); while every extra liter of milk adds 1.9 percentage points (p < 0.01). Participation in crop farming raises the probability by 23.7 percentage points (p < 0.01), reflecting how income diversification supports cooperative engagement. Importantly, farmers facing constraints in accessing veterinary services are 94.1 percentage points more likely to join cooperatives (p < 0.01), underscoring the value of cooperatives in providing livestock support. The model shows good explanatory strength (Pseudo R² = 0.286; Wald chi² = 503.87, p < 0.01). These findings highlight the need for gender-inclusive strategies, expanded veterinary services, and policies promoting integrated farming. Strengthening cooperative frameworks can improve participation and drive inclusive growth in Tanzania’s dairy sector. Int. J. Agril. Res. Innov. Tech. 15(2): 154-164, Dec 2025